The chrysanthemum throne a history of the emperors of Japan - Martin, Peter (University of Hawai'i Press, 1997)
The Chrysanthemum Throne tells a fascinating story of the ebb and flow of the fortunes of the Japanese imperial dynasty, often mere puppets manipulated by the real wielders of power - the feudal warlords and later the shoguns.